Conception of an integrated flowsheet for rare earth elements recovery from coal coarse refuse. (15th June 2018) - Honaker, Rick Q.; Zhang, Wencai; Yang, Xinbo; Rezaee, Mohammad
Highlights: Coarse coal refuse leachates contain elevated levels of critical rare earth elements. Laboratory leaching using 1.2 M sulfuric acid solution recovered 80% of the REEs. Leaching was selective toward heavy REEs as well as scandium. Differential mineral solubility provided high REE recovery and low solids loss. A REE recovery circuit flowsheet utilizing heap leaching was developed. Abstract: The majority of rare earth elements (REEs) existing in the feed to coal preparation plants report to the coarse refuse streams which are transported for permanent storage in contained piles. In this study, an integrated flowsheet was developed based on laboratory test data which combines physical separation, pyrite bio-oxidization, heap leaching, selective precipitation and solvent extraction processes. The test data was obtained from (1) characterization of a number of natural leachate and solid samples collected from different preparation plants which process coals from a number of coal seams and (2) laboratory acid leaching and selective precipitation tests results. The highly-valued critical REEs (i.e., Y, Nd, Eu, Tb and Dy) were selectively leached from the refuse samples in the natural environment due to the acid generated by pyrite oxidization. The leachate samples were evaporated to remove water and obtain residual solids (i.e., dissolved solids in the leachates). The total REE content in the dissolved solids from a given leachate sample was 380 ppm, which was higher than the REE content of the coarse refuse material that generated the leachate (322 ppm). Acid leaching tests recovered as much as 80% of the total REEs from the coarse refuse samples using a 1.2 M sulfuric acid solution. Afterwards, the pH of the leachate was increased in a step-wise fashion which resulted in the production of precipitates containing 0.3–1.1% total REEs. A significant amount of contaminants, such as Fe, Al, and Ca, were eliminated in the sequential precipitation process, which allowed further upgrading using oxalic acid precipitation and/or solvent extraction. In the proposed flowsheet, the coarse refuse is arranged in heap leach pads and the acid needed for REE leaching is primarily produced from pyrite bio-oxidization, which enhances the selectivity of REE recovery and significantly reduces the cost. The successful application of the flowsheet would result in significant benefits to both the coal and rare earth industries.